ANALYSIS OF FACTORS AFFECTING MSMEs NOT IMPLEMENTING THE PREPARATION OF FINANCIAL STATEMENTS BASED ON EMKM SAK IN NORTH TIMOR CENTRAL DISTRICT (CASE STUDY ON Msmes IN TTU DISTRICT) - Marce Sherly Kase (SEAN Institute, 2022)
This study aims to determine the application of SAK EMKM to micro, small and medium enterprises in North Central Timor District. The study was conducted to find out the practice of recording financial reports by these MSMEs, as well as the factors that led to the non-implementation of SAK EMKM-based financial records for MSMEs registered with the Office of Cooperatives and MSMEs. This type of research is a qualitative research, that is, directly involved in the field related to what is being done leads to the description and application of SAK EMKM-based financial records by conducting interviews and taking financial reports to be processed so that they are in accordance with SAK EMKM. The subjects in this study were 28 informants who owned Micro, Small and Medium Enterprises to see if the practice of implementing financial records was presented in accordance with SAK EMKM or not, which then referred to the theory of accounting systems related to financial records that were generally accepted. The results of field observations based on interviews show that as many as 80% of SMEs in TTU Regency are in the trading business sector and still do not have the ability to present financial information in accordance with SAK EMKM.